The expression of genes TLR2 and TLR10 in the gastric tissue of patients with gastroduodenal disorders caused by Helicobacter pylori (Baghdad Science Journal, 2024)
The bacterium Helicobacter pylori (H. pylori) is the key etiological agent in gastritis, peptic ulcer, and gastric cancer disease. Toll-like receptors (TLRs) contribute to the innate immune response through pathogen-associated molecular patterns (PAMPs) derived from H. pylori and other microorganisms as well as damage-associated molecular patterns (DAMPs) derived from host cells, such as tumour cells, dead or dying cells, or products released from cells in response to signals such as hypoxia. The study involved gastric biopsies taken from 88 gastroduodenal disorder patients and 21 healthy individuals. The clinical diagnoses of these groups after endoscopy examination included gastritis, peptic ulcers, and gastric cancer. The detection of H. pylori infection was performed using PCR to amplify ureC and ureA genes, then the bands were visualized by gel electrophoresis. The expression of TLR2 and TLR10 genes in gastric biopsies was evaluated using the relative method. The current findings indicate that susceptibility to gastroduodenal disorder increases with age, as most of the patients were over 30 years old (68 out of 88 patients) representing 77.2% of patients.  The bacterium induced the expression of TLR2 and TLR10 genes, the gene TLR2 was recorded 11.11-fold in patients with gastritis, 7. 65-fold in those with peptic ulcer, and 6.25-fold in patients suffering from gastric cancer, the folding decreased with the prognosis of the disease. On the other hand, the TLR10 gene recorded the highest value 5.01-fold in peptic ulcer patients, followed by 4.73-fold with gastritis, and 3.10-fold with gastric cancer. The expression of the TLR2 and TLR10 genes was significantly higher (p ≤ 0.01) in the patients’ group compared with the control one.  In gastritis, peptic ulcer, and gastric cancer patients, the TLR2 and TLR10 gene expression was higher than in the healthy group, and TLR2 was higher than TLR10.